Pembangunan Berkelanjutan pada Kawasan Benteng Nieuw Victoria Menggunakan Konsep Triple Bottom Line (TBL) - Samuel Michael Wattimury; Kurniawati Kurniawati (Badan Riset dan Inovasi Nasional (BRIN), 2022)
Fort Nieuw Victoria is one of the cultural heritages in Ambon City, however, up until now it still functions as the headquarters of the Pattimura Regional Military Command XVI which has caused the function of the fort as a cultural heritage building to be invisible, in the attempt of restoring the Fort Nieuw Victoria's function as a cultural heritage building, the Ambon City government has coordinated with the Ministry of Education and Culture, the Ministry of Defense, also the TNI Commander, unfortunately until recently the city government has not prepared a final model for the development of the cultural heritage building. This paper aimed to provide input on the sustainable development of the Fort Nieuw Victoria area. Using qualitative methods through a descriptive approach is expected to answer the problems and reaching the purpose of this paper. The results of this study show that by using the triple bottom line concept, in the sustainable development at Fort Nieuw Victoria it’s not only as tourist destination to increase local revenue (economic side), but also make it a green open space as a provider of oxygen for urban communities (ecology), and can be used as a space of education, recreation, a gathering place for young people (social side)